Biotransformation of andrographolide using tropical versus psychrotolerant fungi as biocatalyst / Nur Shahirah Shaharudin ... [et al.] - Shaharudin, Nur Shahirah; Abdul Halim, Muhammad Hatta Syahiran; Surindar Singh, Gurmeet Kaur; Ali Shah, Syed Adnan; Teh, Lay Kek; Sultan, Sadia (Faculty of Applied Sciences, 2024)
Andrographolide, a labdane diterpenoid compound, is known to have a wide range of biological properties, including anti-inflammatory, antibacterial, anticancer, antidiabetic, antimalarial, and hepatoprotective effects. Biotransformation of andrographolide is a promising method for discovering new drugs to treat various diseases. This study aims to ferment andrographolide with chosen fungal strains and to subject the cultured extract to HPLC analysis. The HPLC profiles between two selected fungi of different biotopes were compared to evaluate their ability to perform biotransformation reactions. To perform this study, andrographolide was fermented using Beauveria bassiana ATCC 74040, a tropical fungus, and R3-2 SP 17, a psychrotolerant fungi. The extraction was carried out after 4, 8, and 12 days of fermentation of andrographolide with each chosen fungi strain. The HPLC profile of the resulting extracts was compared and analyzed with the HPLC profiles of starting material, positive and negative controls. The appearance of a new peak in the HPLC profiles of the resulting extracts indicated the presence of a biotransformed metabolite of andrographolide. After comparing the HPLC profile of the resulting extract between tropical and psychrotolerant fungus, it is indicated that the psychrotolerant fungus, R3-2 SP 17, showed more promising results in the discovery of new chemical derivatives. This study would aid people, especially in the pharmaceutical field, discover a new drug to overcome infectious diseases and cancer.